Kesetaraan Bukan Keadilan, Kritik Maqashid Syariah terhadap Tafsir Feminis atas Pembagian Waris 2:1 - Ahmad Eko; Muhammad Nur Al Isro; Nauval Ar rosyid (Sharia Faculty of Universitas Islam Negeri Maulana Malik Ibrahim Malang, Indonesia, 2026)
Discussions regarding the 2:1 inheritance ratio remain prominent in Islamic Legal Studies. This ratio, as given in the Qur’an (4:11), is also the central focus of many Muslim feminists concerned with its relevance to inheritance claims. They argue that the ratio no longer reflects social justice since modern social arrangements advocate more egalitarian norms. These feminists rely on interpretive approaches that frame the ratio as a product of historical/legal patriarchy, emphasizing the need to reformulate legal texts and viewing the ratio as an example of archaic patriarchy in contemporary legal feminism. However, they fail to explain that historical legal patriarchy, as a textual artifact, possesses its own ontology and that revealed texts hold authoritative status in constructing Islamic legal theory.In contrast, the justice of maqasid syariah holds that justice must be understood in relation to, not separate from, the dimensions of law, obligation, economic structure, society, and the values the law seeks to uphold. Critiquing the 2:1 ratio cannot be done apart from these economic, social, and protective dimensions of the legal tradition. This article aims to systematically engage these debates, assessing how far feminist critiques can be accommodated and identifying possible reforms that do not contradict foundational legal principles.